2019
DOI: 10.31217/p.33.1.11
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Problematic Issues in Logistics Cost Management

Abstract: Logistics cost management is associated with certain specific challenges, since increasing the quality of logistics services for customers often comes with increased logistics costs. In addition, reducing the costs of one logistic component causes an increase in the costs of another logistic component, which results in higher total logistics costs. Various cost models have been developed to support the optimisation of logistics activities, which represent the main focus of research and a key practical tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Bontempo et al [35] Logistics costs It is defined as all expenses for moving goods in the urban context. Muha [46] The survey was administered over the internet. An invitation was sent to professionals to participate in the study, including an informed consent statement that communicated that the participants authorized the researchers to use their responses anonymously.…”
Section: Construct Description Referencesmentioning
confidence: 99%
“…Bontempo et al [35] Logistics costs It is defined as all expenses for moving goods in the urban context. Muha [46] The survey was administered over the internet. An invitation was sent to professionals to participate in the study, including an informed consent statement that communicated that the participants authorized the researchers to use their responses anonymously.…”
Section: Construct Description Referencesmentioning
confidence: 99%
“…Increasing the quality of logistics services usually results in an increase in their price. Following this fact, one of the goals of creating cost models is ensuring that the increase in costs does not exceed an acceptable level [16]. This paper provides an analysis of the problem of minimizing servicing costs…”
Section: Related Workmentioning
confidence: 99%
“…Muha [19] determined the scope of the optimization of individual logistics models from the point of view of how individual costs categories and processes are treated. As a result, it was found that the lack of a uniform definition or standard to unify individual logistics costs and the knowledge of logistics costs are the main factors that affect the level of difficulty in managing logistics costs.…”
Section: Review Of the Literaturementioning
confidence: 99%